Efficacy of Ceftazidime and Cefepime in the Management of COVID-19 Patients: Single Center Report from Egypt - Ragaey A. Eid; Marwa O. Elgendy; Ahmed O. El-Gendy; Sara O. Elgendy; Lassaad Belbahri; Ahmed M. Sayed; Mostafa E. Rateb (MDPI AG, 2021)
The purpose of this study was to explore the value of using cefepime and ceftazidime in treating patients with COVID-19. A total of 370 (162 males) patients, with RT-PCR-confirmed cases of COVID-19, were included in the study. Out of them, 260 patients were treated with cefepime or ceftazidime, with the addition of steroids to the treatment. Patients were divided into three groups: Group 1: patients treated with cefepime (124 patients); Group 2: patients treated with ceftazidime (136 patients); Group 3 (control group): patients treated according to the WHO guidelines and the Egyptian COVID-19 management protocol (110 patients)/ Each group was classified into three age groups: 18-30, 31-60, and >60 years. The dose of either cefepime or ceftazidime was 1000 mg twice daily for five days. Eight milligrams of dexamethasone were used as the steroidal drug. Careful follow-ups for the patients were carried out. In vitro and in silico Mpro enzyme assays were performed to investigate the antiviral potential of both antibiotics. The mean recovery time for Group 1 was 12 days, for Group 2 was 13 days, and for Group 3 (control) was 19 days. No deaths were recorded, and all patients were recovered without any complications. For Group 1, the recovery time was 10, 12, and 16 days for the age groups 18-30, 30-60, and >60 years, respectively. For Group 2, the recovery time was 11, 13, and 15 days for the age groups 18-30, 30-60, and >60 years, respectively. For Group 3 (control), the recovery time was 15, 16, and 17 days for the age groups 18-30, 30-60, and >60 years, respectively. Both ceftazidime and cefepime showed very good inhibitory activity towards SARS CoV-2's Mpro, with IC50 values of 1.81 µM and 8.53 µM, respectively. In conclusion, ceftazidime and cefepime are efficient for the management of moderate and severe cases of COVID-19 due to their potential anti-SARS CoV-2 activity and low side effects, and, hence, the currently used complex multidrug treatment protocol can be replaced by the simpler one proposed in this study.